2019
DOI: 10.1007/s13762-019-02505-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dewatering of polymer-rich aerobic granular sludge with cationic polymer containing hydrocarbons

Abstract: This study compared the dewatering properties of aerobic granular and activated sludge from full-scale wastewater treatment plants, and determined how polymer dose and type affect granular sludge dewatering efficiency. At the same dose, granular sludge filtration cake had about 4% lower humidity than activated sludge cake. Aerobic stabilization improved only activated sludge dewatering. The granular sludge reactor had over 1.5 times more extracellular polymeric substances (1.8 times more alginate) per reactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…3 a). These values were slightly higher than the ALP-AGS content reported in another study conducted in a full-scale WWTP 30 and similar to values observed in lab-scale reactors, which are usually higher than in full-scale systems 23 . For example, in lab-scale reactors fed with primary effluent from municipal wastewater, AGS contained 184 ± 18 mg VS ALP/g VSS 9 .…”
Section: Resultssupporting
confidence: 80%
“…3 a). These values were slightly higher than the ALP-AGS content reported in another study conducted in a full-scale WWTP 30 and similar to values observed in lab-scale reactors, which are usually higher than in full-scale systems 23 . For example, in lab-scale reactors fed with primary effluent from municipal wastewater, AGS contained 184 ± 18 mg VS ALP/g VSS 9 .…”
Section: Resultssupporting
confidence: 80%
“…In contrast, it was reported that the Ps content is positively associated with dewaterability [69]. So, a lower PN/Ps ratio means a higher dewaterability [4,61]. Zhang et al [70] and Jahn et al [24] indicated that the presence of tightbound EPS significantly limits granules dewaterability since it contains the majority of PN content.…”
Section: Dewaterability Of Excess Granular Sludgementioning
confidence: 98%
“…[ [86][87][88][89][90][91] It can be injected as bio-flocculants in combination with multivalent cations for sludge dewatering. [4,82,83] EPS can be used as bio-absorbent for metal removal from industrial wastes. [94][95][96][97] Removal of toxic organic compounds.…”
Section: Excess Granular Sludge and Circular Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Extractable ALE can comprise up to 25% of AGS [37]; extraction of ALE can, therefore, decrease the solids content of AGS and contribute to sludge management [49]. In a study by Cydzik-Kwiatkowska et al [50], the content of ALE was about 184 mg/L of excess activated sludge, whereas the amount of ALE in granular sludge was over three times higher. The amount of ALE per g unit of biomass was over twofold higher in AGS (86.0 ± 11.2 mg/g MLSS) than in activated sludge (49.0 ± 9.0 mg/g MLSS).…”
Section: Composition Of Polymers In Biomassmentioning
confidence: 99%